Causal effects of gut microbiota on chalazion: a two-sample Mendelian randomization study - Zhang, Wenfei; Gu, Xingwang; Zhao, Qing; Wang, Chuting; Liu, Xinyu; Chen, Youxin; Zhao, Xinyu (Frontiers in Medicine, 2024)
Purpose: To investigate the causal relationship between gut microbiota (GM) and chalazion through mendelian randomization (MR) analysis. Methods: GM-related genome-wide association studies (GWAS) were obtained from the International Consortium MiBioGen. Genetic data for chalazion were sourced from the MRC Integrative Epidemiology Unit (IEU) Open GWAS database. Five MR methods, including inverse variance weighted (IVW), were employed to estimate causal relationships. Cochran’s Q test was used to detect heterogeneity, the MR-Egger intercept test and MR-PRESSO regression were utilized to detect horizontal pleiotropy, and the leave-one-out method was employed to validate data stability. Results: We identified 1509 single nucleotide polymorphisms (SNPs) across 119 genera as instrumental variables (IVs) (P<1×10–5). According to the inverse variance weighted (IVW) estimate, the Family XIII AD3011 group (OR=1.0018, 95% CI 1.0002-1.0035, P=0.030) and Catenibacterium (OR=1.0013, 95% CI 1.0002-1.0025, P=0.022) were potentially associated with increased risk of chalazion. Conversely, Veillonella (OR=0.9986, 95% CI 0.9974-0.9999, P=0.036) appeared to provide protection against chalazion. There was no evidence of heterogeneity or pleiotropy. Conclusion: This study uncovered the causal relationship between GM and chalazion, pinpointing Catenibacterium and Family XIII AD3011 group as potential risk contributors, while highlighting Veillonella as a protective factor. In-depth investigation into the potential mechanisms of specific bacteria in chalazion was essential for providing novel therapeutic and preventive strategies in the future.